Nano modified negative hydrogen sheet and preparation method thereof

By optimizing the preparation process of negative hydrogen oyster nano powder and designing composite sustained-release membranes, combined with advanced granulation and coating processes, the antioxidant activity and bioavailability of negative hydrogen sheets are significantly improved, and the storage and utilization of negative hydrogen ions are solved. The problem has broad application prospects.

CN119424350APending Publication Date: 2025-02-14RIZHAOLIFEVALLEYBIOTEHNOIOGYDEVEOPENT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411507733.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The preparation and storage of negative hydrogen ions face many challenges, and it is difficult for the prior art to effectively prepare, store and utilize negative hydrogen ions.

Method used

By optimizing the preparation process of negative hydrogen oyster nano powder, subcritical water purification, alkali coating, high-temperature calcination and other treatments, its specific surface area and activity are improved. A composite sustained-release membrane composed of gelatin, sodium alginate, glyceride, etc. was designed to effectively control the sustained-release and absorption of negative hydrogen ions. Advanced processes such as high-speed shear granulation and coated tableting are adopted to further optimize the preparation process of negative hydrogen sheets.

Benefits of technology

The antioxidant activity of negative hydrogen sheets was significantly improved, and the DPPH radical scavenging rate reached 94%, an increase of 16.4-36.4 percentage points compared with the prior art. In the mouse model of alcoholic liver injury, antioxidant enzyme activity in liver tissue was significantly improved, triglyceride levels were reduced, and steatosis in liver cells was reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005104497650000031
    Figure BDA0005104497650000031
  • Figure BDA0005104497650000032
    Figure BDA0005104497650000032
  • Figure BDA0005104497650000033
    Figure BDA0005104497650000033
Patent Text Reader

Abstract

The invention discloses a nano modified negative hydrogen sheet and a preparation method thereof, and relates to the field of negative hydrogen materials. The nano modified negative hydrogen sheet is prepared from the following raw materials in parts by weight: 90-110 parts of negative hydrogen oyster nano micro powder; 200 to 240 parts of a sustained release film; 20 to 40 parts of starch; and 2-10 parts of magnesium stearate. The preparation process of the negative hydrogen tablet is optimized by adopting advanced processes such as high-speed shearing granulation, accurate coating and tabletting, so that the stability and the consistency of the product quality are further ensured. The nano-modified negative hydrogen tablet provided by the invention has remarkable innovativeness and practical value, can effectively overcome the problems of low activity, poor slow release, low absorption rate and the like of the existing negative hydrogen health care product, and has wide application prospects in improving the oxidation resistance of a human body, delaying senescence and preventing and treating related diseases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of negative hydrogen materials, and in particular to a nano-modified negative hydrogen sheet and a preparation method thereof. Background Art

[0002] As a special type of hydrogen ion, negative hydrogen ions have attracted much attention due to their unique chemical properties and biological effects. Negative hydrogen ions are negative ions formed by hydrogen atoms gaining an extra electron, and have extremely strong reducing and antioxidant abilities. In nature, negative hydrogen ions usually exist in a bound state in certain compounds, such as reduced nicotinamide adenine dinucleotide (NADH). NADH plays an important role in redox reactions in organisms and participates in energy metabolism as an electron donor.

[0003] The biochemical effects of negative hydrogen ions are as follows:

[0004] Antioxidant capacity: The antioxidant capacity of negative hydrogen ions is one of their most significant properties. It can effectively neutralize free radicals and prevent cells from oxidative damage. Free radicals are active molecules produced during the metabolic process in organisms. Excessive free radicals can cause damage to cell membranes, proteins and DNA, leading to a variety of diseases. Negative hydrogen ions neutralize these free radicals by providing additional electrons, thereby protecting cells from oxidative stress.

[0005] Role in energy metabolism: In the process of energy metabolism, negative hydrogen ions play an important role by participating in the synthesis and conversion of ATP (adenosine triphosphate). ATP is the main energy currency in cells and directly participates in various physiological activities of cells. In the process of glucose metabolism, although the amount of ATP directly produced is limited, a large amount of ATP can be generated through NADH and the electron transport chain to meet the energy needs of cells.

[0006] Promoting cell repair and regeneration: Due to its small molecular structure and high permeability, negative hydrogen ions can quickly enter cells and participate in cell repair and regeneration. It can improve cell metabolism, increase cell vitality, and promote the repair of tissues and organs. This characteristic makes negative hydrogen ions have potential application value in the medical field, such as promoting wound healing and improving tissue regeneration.

[0007] Wide range of biological effects: Negative hydrogen ions can not only play an antioxidant and energy carrier role in the body, but also regulate enzyme activity and nucleic acid modification. Due to its tiny size and extremely light weight, negative hydrogen ions can easily penetrate biological membranes and enter various tissues of the human body, including the liver, heart, lungs, kidneys, and brain. This enables it to form a special biological environment in the body, which helps maintain the body's health.

[0008] Although negative hydrogen ions have significant biological effects, their preparation and storage face many challenges. In nature, negative hydrogen ions are difficult to exist alone, mainly because they are very easy to react with other elements or molecules to form more stable compounds. Therefore, how to effectively prepare, store and utilize negative hydrogen ions has become an important topic of concern to researchers. Development of preparation methods: At present, many methods have been used to prepare negative hydrogen materials, including electrolysis, chemical reduction and photocatalysis. These methods have their own advantages and disadvantages. For example, electrolysis can produce water rich in negative hydrogen ions by electrolyzing water, but the efficiency is low; chemical reduction uses a reducing agent to convert hydrogen into negative hydrogen ions, but the reaction conditions need to be controlled to increase the yield; photocatalysis uses a photocatalyst to decompose water into hydrogen under light, part of which can be converted into negative hydrogen ions. Application of nanotechnology: The development of nanotechnology provides a new way to improve the performance of negative hydrogen materials. By nano-modifying traditional materials, their surface area, reaction activity and hydrogen storage capacity can be significantly improved. For example, nano-structuring magnesium-based materials can improve their hydrogen absorption and desorption kinetics. In addition, by combining nanomaterials with other functional materials, their ability to store and release negative hydrogen ions can be further enhanced. Innovation in storage technology: In order to overcome the storage difficulties caused by the high activity of negative hydrogen ions, researchers have developed a variety of storage technologies. For example, by encapsulating negative hydrogen materials in inert gases or liquids to reduce their contact with oxygen or moisture in the environment. In addition, some new materials such as metal organic frameworks (MOFs) and graphene are also used to store negative hydrogen ions. These materials have excellent adsorption properties and good stability.

[0009] With the deepening of research on negative hydrogen materials, they have shown broad application prospects in many fields. In the medical field, negative hydrogen materials can be used to develop new antioxidants, therapeutic agents and health products; in the energy field, they can be used as efficient energy storage materials for fuel cells and other clean energy technologies. In addition, in terms of environmental protection, the degradation of pollutants by using negative hydrogen materials is also an important research direction. Summary of the invention

[0010] In view of this, the purpose of the present invention is to propose a nano-modified negative hydrogen tablet and a preparation method thereof. The nano-modified negative hydrogen tablet of the present invention can effectively remove free radicals in the body, reduce the damage of oxidative stress to the liver, and enhance the antioxidant capacity of the liver by increasing the activity of antioxidant enzymes such as glutathione peroxidase (GPx), glutathione reductase (GRd) and superoxide dismutase (SOD) in the liver, thereby playing an auxiliary protective role against chemical liver damage; enhance immunity: negative hydrogen ions can activate cells and promote the metabolism of the human body, thereby enhancing the immune function of the body; the nano-modified negative hydrogen tablet of the present invention can continuously enhance the human immune system and improve the ability to resist diseases by providing a stable source of negative hydrogen ions. Delay aging: negative hydrogen ions have strong antioxidant capacity, can remove excess free radicals in the body at any time, slow down cell oxidative damage, and thus achieve the effect of delaying aging. The nano-modified negative hydrogen tablet of the present invention can continuously release negative hydrogen ions to provide long-term anti-aging protection for the human body.

[0011] The technical solutions adopted are:

[0012] A nano-modified negative hydrogen sheet is prepared from the following raw materials in parts by weight:

[0013]

[0014] The nano-modified negative hydrogen sheet is prepared from the following raw materials in parts by weight:

[0015]

[0016] The nano-modified negative hydrogen sheet is prepared from the following raw materials in parts by weight:

[0017]

[0018] The negative hydrogen oyster nano powder is prepared by the following method:

[0019] Fresh oyster shells are cleaned and placed in subcritical water for purification to remove surface organic matter and heavy metals, wherein the purification treatment is carried out under the conditions of pressure 1.5-15MPa and temperature 180-350℃ for 2-6h, and the purified oyster shells are dried and crushed into particles below 500μm to obtain oyster shell powder; the oyster shell powder is mixed with 2.5-20wt% calcium hydroxide slurry at a weight volume ratio of 0.1-1, and coated for 2-4h to obtain alkali-coated oyster shell powder; the alkali-coated oyster shell powder is placed at a high temperature of 900-1200℃ and calcined for 3-6h to convert it into calcium oxide powder with a core-shell structure, wherein the core part is oyster shell powder. Calcium oxide microparticles converted from oyster shells, wherein the shell part is calcium oxide nanoparticles converted from calcium hydroxide; the calcined calcium oxide powder is ground to reach a nanometer level with an average particle size of 5-10 μm to obtain nanometer-level oyster shell powder; the nanometer-level oyster shell powder is mixed with lecithin E322 and bamboo charcoal powder in a mass ratio of 1:(2-10):(4-5), and ultrasonically dispersed to form a suspension; the suspension is placed in a closed container with magnesium hydride on the bottom for reaction, so that the powder absorbs and enriches hydrogen; an acid-base regulator is added to the hydrogen-enriched suspension to adjust the pH to a weak alkaline of 7.5-8.5; the pH-adjusted suspension is stirred at a low speed, and vacuum freeze-dried to obtain the product.

[0020] The sustained-release film is prepared by the following method:

[0021] Prepare gelatin, sodium alginate, glyceride, citric acid and bean curd residue in a mass ratio of (30-50):(5-8):(2-3):(1-5):(2-6), add purified water 5-10 times the mass of gelatin, stir and swell at 40-60°C for 2-4 hours to obtain a uniform modified gelatin solution, place the modified gelatin solution in a vacuum degassing machine, degas at 0.08-0.1MPa for 20-40 minutes, evenly coat the modified gelatin solution on a clean glass plate, control the coating thickness to 200-500μm, the coating speed to 5-10cm / s, and dry at 40-60°C for 2-6 hours until the moisture content of the film layer is ≤10%.

[0022] The starch is corn starch.

[0023] A method for preparing the nano-modified negative hydrogen sheet comprises the following steps:

[0024] The negative hydrogen oyster nano powder, sustained-release film and starch are uniformly mixed and granulated, and then magnesium stearate is added for coating and tableting is performed.

[0025] The preparation method of the nano-modified negative hydrogen sheet, wherein the mixing time is 20-30 minutes;

[0026] The weight of water added during the granulation process is 30-50% of the total weight of other substances;

[0027] The granulation equipment is a high-speed shearing machine, and the granulation time is 5-15 minutes.

[0028] The preparation method of the nano-modified negative hydrogen sheet, wherein the coating time is 3-5 minutes, and the coating thickness is 0.2mm-0.5mm.

[0029] The preparation method of the nano-modified negative hydrogen tablets, wherein the tablet pressing equipment is a rotary tablet press, the tablet pressing pressure is 100-300MPa, the tablet weight is controlled to be 500-1000mg, and the tablet pressing speed is 20-50rpm.

[0030] In summary, the beneficial effects of the present invention are:

[0031] The present invention significantly improves the antioxidant activity of negative hydrogen tablets by optimizing the preparation process of negative hydrogen oyster nanopowder and the composition of the sustained-release membrane. The experimental results show that the DPPH free radical scavenging rate of the nano-modified negative hydrogen tablets prepared by the present invention is as high as 92.5-94.0%, which is 16.4-36.4 percentage points higher than the prior art. This significant improvement is mainly attributed to the following aspects:

[0032] 1. Critical water purification treatment: removes organic matter and heavy metals on the surface of oyster shells, improving the purity of raw materials.

[0033] 2. Alkali coating and high temperature calcination: Calcium oxide powder with a core-shell structure is formed, which increases the specific surface area and activity.

[0034] 3. Nano-grinding: The particle size of the powder is controlled in the range of 5-10μm, which further improves the reaction activity.

[0035] 4. Composite sustained-release membrane design: The composite sustained-release membrane composed of gelatin, sodium alginate, glyceride, etc. effectively controls the sustained-release and absorption of negative hydrogen ions.

[0036] The results of animal experiments confirmed that the nano-modified negative hydrogen tablets of the present invention have a significant auxiliary protective effect on alcoholic liver damage:

[0037] 1. Improved antioxidant capacity: The content of reduced glutathione (GSH) in the liver homogenate of mice in each dose group was significantly increased (P<0.01), indicating that the antioxidant capacity of the liver was enhanced.

[0038] 2. Improvement of lipid metabolism: The triglyceride (TG) level in the liver homogenate of mice in each dose group was significantly reduced (P<0.01), indicating that negative hydrogen tablets help improve liver lipid metabolism.

[0039] 3. Hepatocyte protection: The results of pathological histological examination showed that the fatty degeneration of hepatocytes in mice in the high- and medium-dose groups was significantly reduced (P<0.05), confirming the protective effect of negative hydrogen tablets on hepatocytes.

[0040] The present invention has also made a number of innovations and optimizations in the preparation process:

[0041] 1. High-speed shear granulation: Use high-speed shearing machine for granulation, control the granulation time to 5-15min, and improve the uniformity and stability of the product.

[0042] 2. Precise coating: The coating time is controlled to be 3-5min and the coating thickness is 0.2-0.5mm, ensuring the effective release of negative hydrogen ions.

[0043] 3. Optimization of tableting process: Using a rotary tablet press, the tableting pressure is controlled at 100-300MPa, the tablet weight is 500-1000mg, and the tableting speed is 20-50rpm, which ensures the consistency of product quality.

[0044] In summary, the nano-modified negative hydrogen tablets of the present invention have significantly improved the antioxidant activity and bioavailability of the product through innovations in raw material preparation, formula design, and process optimization. Its auxiliary protective effect on alcoholic liver damage has been strongly confirmed by animal experiments, providing new ideas and methods for the development of efficient antioxidant health products. This technology is not only expected to be widely used in the field of health products, but may also provide new options for the prevention and auxiliary treatment of related diseases. DETAILED DESCRIPTION

[0045] The present invention is described in detail below through specific examples, but the use and purpose of these exemplary implementation modes are only used to illustrate the present invention, and do not constitute any form of limitation on the actual protection scope of the present invention, nor limit the protection scope of the present invention to them.

[0046] Example 1

[0047] The nano-modified negative hydrogen sheet is prepared from the following raw materials in parts by weight:

[0048]

[0049] The negative hydrogen oyster nano powder is prepared by the following method:

[0050] Fresh oyster shells were cleaned and placed in subcritical water for purification to remove surface organic matter and heavy metals, wherein the purification treatment was carried out under the conditions of 1.5 MPa pressure and 350°C temperature for 2 hours, and the purified oyster shells were dried and crushed to particles below 500 μm to obtain oyster shell powder; the oyster shell powder was mixed with 2.5 wt% calcium hydroxide slurry at a weight volume ratio of 1, and coated for 2 hours to obtain alkali-coated oyster shell powder; the alkali-coated oyster shell powder was calcined at a high temperature of 1200°C for 3 hours to convert it into calcium oxide powder with a core-shell structure, wherein the core part is the oyster shell converted Calcium oxide microparticles, wherein the shell part is calcium oxide nanoparticles converted from calcium hydroxide; the calcined calcium oxide powder is ground to reach a nanometer level with an average particle size of 5 μm to obtain nano-sized oyster shell powder; the nano-sized oyster shell powder is mixed with lecithin E322 and bamboo charcoal powder in a mass ratio of 1:10:4, and ultrasonically dispersed to form a suspension; the suspension is placed in a closed container with magnesium hydride on the bottom to react, so that the powder absorbs and enriches hydrogen; an acid-base regulator is added to the hydrogen-enriched suspension to adjust the pH to a weak alkaline of 8.5; the pH-adjusted suspension is stirred at a low speed, and vacuum freeze-dried to obtain the product.

[0051] The sustained-release film is prepared by the following method:

[0052] Prepare gelatin, sodium alginate, glyceride, citric acid and tofu dregs in a mass ratio of 30:8:2:5:2, add purified water 10 times the mass of gelatin, stir and swell at 40°C for 4 hours to obtain a uniform modified gelatin solution, place the modified gelatin solution in a vacuum degassing machine, degas at 0.08MPa for 40 minutes, evenly coat the modified gelatin solution on a clean glass plate, control the coating thickness to 200μm, the coating speed to 10cm / s, and dry at 40°C for 6 hours until the moisture content of the film layer is ≤10%.

[0053] The starch is corn starch.

[0054] The preparation method of the nano-modified negative hydrogen sheet comprises the following steps:

[0055] After the negative hydrogen oyster nanopowder, sustained-release film and starch are evenly mixed, granulated, and then magnesium stearate is added for coating, and tablets are obtained. The mixing time is 20 minutes; the weight of water added during the granulation process is 50% of the total weight of other substances; the granulation equipment is a high-speed shearing machine, and the granulation time is 5 minutes. The coating time is 5 minutes, and the coating thickness is 0.2 mm. The tableting equipment is a rotary tablet press, the tableting pressure is 300 MPa, the tablet weight is controlled to be 500 mg, and the tableting speed is 50 rpm.

[0056] Example 2

[0057] The nano-modified negative hydrogen sheet is prepared from the following raw materials in parts by weight:

[0058]

[0059] The negative hydrogen oyster nano powder is prepared by the following method:

[0060] Fresh oyster shells were cleaned and placed in subcritical water for purification to remove surface organic matter and heavy metals, wherein the purification treatment was carried out under the conditions of 15MPa pressure and 180°C temperature for 6h, and the purified oyster shells were dried and crushed to particles below 500μm to obtain oyster shell powder; the oyster shell powder was mixed with 2.5wt% calcium hydroxide slurry at a weight volume ratio of 1, and coated for 2h to obtain alkali-coated oyster shell powder; the alkali-coated oyster shell powder was calcined at a high temperature of 1200°C for 3h to convert it into calcium oxide powder with a core-shell structure, wherein the core part is the oyster shell converted Calcium oxide microparticles, wherein the shell part is calcium oxide nanoparticles converted from calcium hydroxide; the calcined calcium oxide powder is ground to reach a nanometer level with an average particle size of 10 μm to obtain nano-sized oyster shell powder; the nano-sized oyster shell powder is mixed with lecithin E322 and bamboo charcoal powder in a mass ratio of 1:2:5, and ultrasonically dispersed to form a suspension; the suspension is placed in a closed container with magnesium hydride on the bottom to react, so that the powder absorbs and enriches hydrogen; an acid-base regulator is added to the hydrogen-enriched suspension to adjust the pH to a weak alkaline of 7.5; the pH-adjusted suspension is stirred at a low speed, and vacuum freeze-dried to obtain the product.

[0061] The sustained-release film is prepared by the following method:

[0062] Prepare gelatin, sodium alginate, glyceride, citric acid and tofu dregs in a mass ratio of 50:5:3:1:6, add purified water 5 times the mass of gelatin, stir and swell at 60°C for 2 hours to obtain a uniform modified gelatin solution, place the modified gelatin solution in a vacuum degassing machine, degas at 0.1MPa for 20 minutes, evenly coat the modified gelatin solution on a clean glass plate, control the coating thickness to 500μm, the coating speed to 5cm / s, and dry at 60°C for 2 hours until the moisture content of the film layer is ≤10%.

[0063] The starch is corn starch.

[0064] The preparation method of the nano-modified negative hydrogen sheet comprises the following steps:

[0065] After the negative hydrogen oyster nanopowder, sustained-release film and starch are evenly mixed, granulated, and then magnesium stearate is added for coating, and tablets are obtained. The mixing time is 30 minutes; the weight of water added during the granulation process is 30% of the total weight of other substances; the granulation equipment is a high-speed shearing machine, and the granulation time is 15 minutes. The coating time is 3 minutes, and the coating thickness is 0.5 mm. The tableting equipment is a rotary tablet press, the tableting pressure is 100MPa, the tablet weight is controlled to be 1000mg, and the tableting speed is 20rpm.

[0066] Example 3

[0067] The nano-modified negative hydrogen sheet is prepared from the following raw materials in parts by weight:

[0068]

[0069] The negative hydrogen oyster nano powder is prepared by the following method:

[0070] Fresh oyster shells were cleaned and placed in subcritical water for purification to remove surface organic matter and heavy metals, wherein the purification treatment was carried out under a pressure of 1.5 MPa and a temperature of 180°C for 2 hours, and the purified oyster shells were dried and crushed to particles below 500 μm to obtain oyster shell powder; the oyster shell powder was mixed with 2.5 wt% calcium hydroxide slurry at a weight volume ratio of 0.1, and coated for 2 hours to obtain alkali-coated oyster shell powder; the alkali-coated oyster shell powder was calcined at a high temperature of 900°C for 3 hours to convert it into calcium oxide powder with a core-shell structure, wherein the core part is the oyster shell conversion The shell part is calcium oxide nanoparticles converted from calcium hydroxide; the calcined calcium oxide powder is ground to reach a nanometer level with an average particle size of 5 μm to obtain nano-sized oyster shell powder; the nano-sized oyster shell powder is mixed with lecithin E322 and bamboo charcoal powder in a mass ratio of 1:2:4, and ultrasonically dispersed to form a suspension; the suspension is placed in a closed container with magnesium hydride on the bottom to react, so that the powder absorbs and enriches hydrogen; an acid-base regulator is added to the hydrogen-enriched suspension to adjust the pH to a weak alkaline of 7.5; the pH-adjusted suspension is stirred at a low speed, and vacuum freeze-dried to obtain the product.

[0071] The sustained-release film is prepared by the following method:

[0072] Prepare gelatin, sodium alginate, glyceride, citric acid and tofu dregs in a mass ratio of 30:5:2:1:2, add purified water 5 times the mass of gelatin, stir and swell at 40°C for 2h to obtain a uniform modified gelatin solution, place the modified gelatin solution in a vacuum degassing machine, degas at 0.08MPa for 20min, evenly coat the modified gelatin solution on a clean glass plate, control the coating thickness to 200μm, the coating speed to 5cm / s, and dry at 40°C for 2h until the moisture content of the film layer is ≤10%.

[0073] The starch is corn starch.

[0074] The preparation method of the nano-modified negative hydrogen sheet comprises the following steps:

[0075] After the negative hydrogen oyster nanopowder, sustained-release film and starch are evenly mixed, granulated, and then magnesium stearate is added for coating, and tablets are obtained. The mixing time is 20 minutes; the weight of water added in the granulation process is 30% of the total weight of other substances; the granulation equipment is a high-speed shearing machine, and the granulation time is 5 minutes. The coating time is 3 minutes, and the coating thickness is 0.2 mm. The tableting equipment is a rotary tablet press, the tableting pressure is 100 MPa, the tablet weight is controlled to be 500 mg, and the tableting speed is 20 rpm.

[0076] Example 4

[0077] The nano-modified negative hydrogen sheet is prepared from the following raw materials in parts by weight:

[0078]

[0079] The negative hydrogen oyster nano powder is prepared by the following method:

[0080] Fresh oyster shells were cleaned and placed in subcritical water for purification to remove surface organic matter and heavy metals, wherein the purification treatment was carried out under a pressure of 15 MPa and a temperature of 350°C for 6 hours, and the purified oyster shells were dried and crushed to particles below 500 μm to obtain oyster shell powder; the oyster shell powder was mixed with 20 wt% calcium hydroxide slurry at a weight volume ratio of 1, and coated for 4 hours to obtain alkali-coated oyster shell powder; the alkali-coated oyster shell powder was calcined at a high temperature of 1200°C for 6 hours to convert it into calcium oxide powder with a core-shell structure, wherein the core part is the oxygen converted from the oyster shell. The shell part is calcium oxide nanoparticles converted from calcium hydroxide; the calcined calcium oxide powder is ground to reach a nanometer level with an average particle size of 10 μm to obtain nano-sized oyster shell powder; the nano-sized oyster shell powder is mixed with lecithin E322 and bamboo charcoal powder in a mass ratio of 1:10:5, and ultrasonically dispersed to form a suspension; the suspension is placed in a closed container with magnesium hydride on the bottom to react, so that the powder absorbs and enriches hydrogen; an acid-base regulator is added to the hydrogen-enriched suspension to adjust the pH to a weak alkaline of 8.5; the pH-adjusted suspension is stirred at a low speed and vacuum freeze-dried to obtain the product.

[0081] The sustained-release film is prepared by the following method:

[0082] Prepare gelatin, sodium alginate, glyceride, citric acid and tofu dregs in a mass ratio of 50:8:3:5:6, add purified water 10 times the mass of gelatin, stir and swell at 60°C for 4 hours to obtain a uniform modified gelatin solution, place the modified gelatin solution in a vacuum degassing machine, degas at 0.1MPa for 40 minutes, evenly coat the modified gelatin solution on a clean glass plate, control the coating thickness to 500μm, the coating speed to 10cm / s, and dry at 60°C for 6 hours until the moisture content of the film layer is ≤10%.

[0083] The starch is corn starch.

[0084] The preparation method of the nano-modified negative hydrogen sheet comprises the following steps:

[0085] After the negative hydrogen oyster nanopowder, sustained-release film and starch are evenly mixed, granulated, and then magnesium stearate is added for coating, and tablets are obtained. The mixing time is 30 minutes; the weight of water added in the granulation process is 50% of the total weight of other substances; the granulation equipment is a high-speed shearing machine, and the granulation time is 15 minutes. The coating time is 5 minutes, and the coating thickness is 0.5 mm. The tableting equipment is a rotary tablet press, the tableting pressure is 300 MPa, the tablet weight is controlled to be 1000 mg, and the tableting speed is 50 rpm.

[0086] Example 5

[0087] The nano-modified negative hydrogen sheet is prepared from the following raw materials in parts by weight:

[0088] 100 portions of negative hydrogen oyster nano powder;

[0089]

[0090] The negative hydrogen oyster nano powder is prepared by the following method:

[0091] Fresh oyster shells were cleaned and placed in subcritical water for purification to remove surface organic matter and heavy metals, wherein the purification treatment was carried out under the conditions of 10MPa pressure and 250℃ for 4h, and the purified oyster shells were dried and crushed to particles below 500μm to obtain oyster shell powder; the oyster shell powder was mixed with 10wt% calcium hydroxide slurry at a weight volume ratio of 0.5, and coated for 3h to obtain alkali-coated oyster shell powder; the alkali-coated oyster shell powder was calcined at 1100℃ for 5h to convert it into calcium oxide powder with a core-shell structure, wherein the core part is the oyster shell converted into calcium oxide powder; The shell part is calcium oxide nanoparticles converted from calcium hydroxide; the calcined calcium oxide powder is ground to reach a nanometer level with an average particle size of 8 μm to obtain nano-sized oyster shell powder; the nano-sized oyster shell powder is mixed with lecithin E322 and bamboo charcoal powder in a mass ratio of 1:6:5, and ultrasonically dispersed to form a suspension; the suspension is placed in a closed container with magnesium hydride on the bottom to react, so that the powder absorbs and enriches hydrogen; an acid-base regulator is added to the hydrogen-enriched suspension to adjust the pH to a weak alkalinity of 8; the pH-adjusted suspension is stirred at a low speed, and vacuum freeze-dried to obtain the product.

[0092] The sustained-release film is prepared by the following method:

[0093] Prepare gelatin, sodium alginate, glyceride, citric acid and tofu dregs in a mass ratio of 40:7:2:3:4, add purified water 8 times the mass of gelatin, stir and swell at 50°C for 3 hours to obtain a uniform modified gelatin solution, place the modified gelatin solution in a vacuum degassing machine, degas at 0.09MPa for 30 minutes, evenly coat the modified gelatin solution on a clean glass plate, control the coating thickness to 400μm, the coating speed to 8cm / s, and dry at 50°C for 4 hours until the moisture content of the film layer is ≤10%.

[0094] The starch is corn starch.

[0095] The preparation method of the nano-modified negative hydrogen sheet comprises the following steps:

[0096] After the negative hydrogen oyster nanopowder, sustained-release film and starch are evenly mixed, granulated, and then magnesium stearate is added for coating, and tablets are obtained. The mixing time is 25 minutes; the weight of water added during the granulation process is 40% of the total weight of other substances; the granulation equipment is a high-speed shearing machine, and the granulation time is 10 minutes. The coating time is 4 minutes, and the coating thickness is 0.4 mm. The tableting equipment is a rotary tablet press, the tableting pressure is 200 MPa, the tablet weight is controlled to be 800 mg, and the tableting speed is 35 rpm.

[0097] Comparative Example 1

[0098] The nano-modified negative hydrogen sheet is prepared from the following raw materials in parts by weight:

[0099]

[0100] The negative hydrogen oyster nano powder is prepared by the following method:

[0101] The negative hydrogen oyster calcium powder is prepared by the following method: treating oyster shell powder with a particle size of 200 mesh at a temperature of 700° C. and under nitrogen protection conditions; treating the treated oyster shell powder at a temperature of 1000° C. and under mixed gas protection conditions of hydrogen and nitrogen to obtain negative hydrogen oyster calcium powder.

[0102] The sustained-release film is prepared by the following method:

[0103] Prepare gelatin, sodium alginate, glyceride, citric acid and tofu dregs in a mass ratio of 40:7:2:3:4, add purified water 8 times the mass of gelatin, stir and swell at 50°C for 3 hours to obtain a uniform modified gelatin solution, place the modified gelatin solution in a vacuum degassing machine, degas at 0.09MPa for 30 minutes, evenly coat the modified gelatin solution on a clean glass plate, control the coating thickness to 400μm, the coating speed to 8cm / s, and dry at 50°C for 4 hours until the moisture content of the film layer is ≤10%.

[0104] The starch is corn starch.

[0105] The preparation method of the nano-modified negative hydrogen sheet comprises the following steps:

[0106] After the negative hydrogen oyster nanopowder, sustained-release film and starch are evenly mixed, granulated, and then magnesium stearate is added for coating, and tablets are obtained. The mixing time is 25 minutes; the weight of water added during the granulation process is 40% of the total weight of other substances; the granulation equipment is a high-speed shearing machine, and the granulation time is 10 minutes. The coating time is 4 minutes, and the coating thickness is 0.4 mm. The tableting equipment is a rotary tablet press, the tableting pressure is 200 MPa, the tablet weight is controlled to be 800 mg, and the tableting speed is 35 rpm.

[0107] Comparative Example 2

[0108] The nano-modified negative hydrogen sheet is prepared from the following raw materials in parts by weight:

[0109]

[0110]

[0111] The negative hydrogen oyster nano powder is prepared by the following method:

[0112] Fresh oyster shells were cleaned and placed in subcritical water for purification to remove surface organic matter and heavy metals, wherein the purification treatment was carried out under the conditions of 10MPa pressure and 250℃ for 4h, and the purified oyster shells were dried and crushed to particles below 500μm to obtain oyster shell powder; the oyster shell powder was mixed with 10wt% calcium hydroxide slurry at a weight volume ratio of 0.5, and coated for 3h to obtain alkali-coated oyster shell powder; the alkali-coated oyster shell powder was calcined at 1100℃ for 5h to convert it into calcium oxide powder with a core-shell structure, wherein the core part is the oyster shell converted into calcium oxide powder; The shell part is calcium oxide nanoparticles converted from calcium hydroxide; the calcined calcium oxide powder is ground to reach a nanometer level with an average particle size of 8 μm to obtain nano-sized oyster shell powder; the nano-sized oyster shell powder is mixed with lecithin E322 and bamboo charcoal powder in a mass ratio of 1:6:5, and ultrasonically dispersed to form a suspension; the suspension is placed in a closed container with magnesium hydride on the bottom to react, so that the powder absorbs and enriches hydrogen; an acid-base regulator is added to the hydrogen-enriched suspension to adjust the pH to a weak alkalinity of 8; the pH-adjusted suspension is stirred at a low speed, and vacuum freeze-dried to obtain the product.

[0113] The sustained-release membrane is gelatin.

[0114] The starch is corn starch.

[0115] The preparation method of the nano-modified negative hydrogen sheet comprises the following steps:

[0116] After the negative hydrogen oyster nanopowder, sustained-release film and starch are evenly mixed, granulated, and then magnesium stearate is added for coating, and tablets are obtained. The mixing time is 25 minutes; the weight of water added during the granulation process is 40% of the total weight of other substances; the granulation equipment is a high-speed shearing machine, and the granulation time is 10 minutes. The coating time is 4 minutes, and the coating thickness is 0.4 mm. The tableting equipment is a rotary tablet press, the tableting pressure is 200 MPa, the tablet weight is controlled to be 800 mg, and the tableting speed is 35 rpm.

[0117] Comparative Example 3

[0118] The nano-modified negative hydrogen sheet is prepared from the following raw materials in parts by weight:

[0119]

[0120]

[0121] The negative hydrogen oyster nano powder is prepared by the following method:

[0122] Fresh oyster shells were cleaned and placed in subcritical water for purification to remove surface organic matter and heavy metals, wherein the purification treatment was carried out under the conditions of 10MPa pressure and 250℃ for 4h, and the purified oyster shells were dried and crushed to particles below 500μm to obtain oyster shell powder; the oyster shell powder was mixed with 10wt% calcium hydroxide slurry at a weight volume ratio of 0.5, and coated for 3h to obtain alkali-coated oyster shell powder; the alkali-coated oyster shell powder was calcined at 1100℃ for 5h to convert it into calcium oxide powder with a core-shell structure, wherein the core part is the oyster shell converted into calcium oxide powder; The shell part is calcium oxide nanoparticles converted from calcium hydroxide; the calcined calcium oxide powder is ground to reach a nanometer level with an average particle size of 8 μm to obtain nano-sized oyster shell powder; the nano-sized oyster shell powder is mixed with lecithin E322 and bamboo charcoal powder in a mass ratio of 1:6:5, and ultrasonically dispersed to form a suspension; the suspension is placed in a closed container with magnesium hydride on the bottom to react, so that the powder absorbs and enriches hydrogen; an acid-base regulator is added to the hydrogen-enriched suspension to adjust the pH to a weak alkalinity of 8; the pH-adjusted suspension is stirred at a low speed, and vacuum freeze-dried to obtain the product.

[0123] The sustained-release film is prepared by the following method:

[0124] Prepare gelatin, sodium alginate and tofu dregs in a mass ratio of 40:3:4, add purified water 8 times the mass of gelatin, stir and swell at 50°C for 3 hours to obtain a uniform modified gelatin solution, place the modified gelatin solution in a vacuum degassing machine, degas at 0.09MPa for 30 minutes, evenly coat the modified gelatin solution on a clean glass plate, control the coating thickness to 400μm, the coating speed to 8cm / s, and dry at 50°C for 4 hours until the moisture content of the film layer is ≤10%.

[0125] The starch is corn starch.

[0126] The preparation method of the nano-modified negative hydrogen sheet comprises the following steps:

[0127] After the negative hydrogen oyster nanopowder, sustained-release film and starch are evenly mixed, granulated, and then magnesium stearate is added for coating, and tablets are obtained. The mixing time is 25 minutes; the weight of water added during the granulation process is 40% of the total weight of other substances; the granulation equipment is a high-speed shearing machine, and the granulation time is 10 minutes. The coating time is 4 minutes, and the coating thickness is 0.4 mm. The tableting equipment is a rotary tablet press, the tableting pressure is 200 MPa, the tablet weight is controlled to be 800 mg, and the tableting speed is 35 rpm.

[0128] test

[0129] Scavenging effect on DPPH free radicals

[0130] Take 2mL of sample and add it to 2mL 0.1mmol / L DPPH solution (dissolved in anhydrous ethanol). After mixing, place it at room temperature for 30min and measure the absorbance (Ai) of each mass concentration sample at 517nm. Parallel determination 3 times, take the average value. Add 2mL anhydrous ethanol to 2mL sample solution and measure absorbance (Aj). In addition, take 2mL anhydrous ethanol instead of sample and add 2mL DPPH free radical solution to measure blank absorbance (Ao). Calculate DPPH free radical scavenging rate according to formula (I).

[0131]

[0132] Table 1 Clearance determination

[0133]

[0134] Comparative Examples 1-3 respectively use traditional negative hydrogen oyster nanopowder, remove the sustained-release membrane, and do not use sodium alginate and glyceride, resulting in their DPPH free radical scavenging ability being significantly lower than that of the embodiments of the present invention. Comparative Example 1 uses negative hydrogen oyster nanopowder prepared by traditional technology, without subcritical water purification and alkali coating, etc., and its specific surface area and activity are low, resulting in poor antioxidant performance, and the DPPH free radical scavenging rate is only 57.6%. Comparative Example 2 removes the sustained-release membrane, so that negative hydrogen ions cannot be effectively sustained-released and absorbed, affecting its antioxidant effect, and the scavenging rate is 73.2%, which is better than Comparative Example 1, but still significantly lower than the embodiments of the present invention. Comparative Example 3 does not use sodium alginate and glyceride, resulting in a decrease in the performance of the sustained-release membrane. Sodium alginate has good film-forming properties and biocompatibility, which can improve the mechanical strength and stability of the sustained-release membrane; glyceride helps to improve the permeability and absorption rate of negative hydrogen ions. The lack of both makes the DPPH free radical scavenging rate of Comparative Example 3 only 80.4%, which is less than the embodiments of the present invention. In summary, through the comparative tests of the embodiments and the comparative examples, it can be seen that the present invention significantly improves the antioxidant activity of the negative hydrogen tablets by optimizing the preparation process of the negative hydrogen oyster nanopowder, the composition and preparation method of the sustained-release membrane, and the DPPH free radical scavenging rate is increased by 16.4-36.4 percentage points compared with the prior art, reaching a high level of 94%, which proves that the technical scheme of the present invention has significant innovation and superiority, and can effectively overcome the problems of low activity, poor sustained release, and low absorption rate of existing negative hydrogen health products, and has important application value for improving the human body's antioxidant capacity, delaying aging, and preventing and treating related diseases.

[0135] The nano-modified negative hydrogen sheet of Example 5 was used for animal testing.

[0136] 1 Materials and methods

[0137] 1.1 Experimental animals: 55 SPF grade Kunming male mice provided by Spectroscopy (Beijing) Biotechnology Co., Ltd.

[0138] 1.2 Experimental grouping and dosage design: 50 male mice with a body weight of 18-22 g adapted for 6 days were randomly divided into three dosage groups, a blank control group and a model control group, a total of five groups, with 10 mice in each group.

[0139] 1.3 Dosage design: Three dose groups were set up: 1.5g / kg.BW, 1.0g / kg.BW, and 0.5g / kg.BW. A blank control group and a model control group were also set up. Anhydrous ethanol (analytical grade) was used to create a liver injury model, with an ethanol concentration of 50% (diluted with pure water) and an intragastric volume of 12mL / kg.BW.

[0140] 1.4 Sample preparation: Weigh 1.5g, 1.0g, and 0.5g of the sample respectively, add pure water to 20mL in turn, dissolve and mix well, and prepare solutions with concentrations of 7.5%, 5.0%, and 2.5% respectively for use.

[0141] 1.5 Experimental method: The alcoholic liver injury model was used. Different doses of samples were given to the three dose groups. The blank control group and the model control group were given the same volume of pure water, which was orally gavaged once a day at 20 mL / kg.BW. The body weight was weighed twice a week, and the dose of the test samples was adjusted according to the body weight. The test samples were given continuously for 30 days. At the end, the model control group and the three dose groups were given 50% ethanol solution by oral gavage once, with a gavage volume of 12 mL / kg.BW. The blank control group was given the same volume of pure water. After fasting for 16 hours, the animals were killed by cervical dislocation. The left lobe of the liver was taken for histopathological examination. The remaining liver was rinsed with 0.9% sodium chloride injection, wiped dry, and the tissue weight was accurately weighed. It was cut into pieces and placed in a homogenizer. At the ratio of weight g: volume mL = 1:9, 0.9% sodium chloride injection was added and placed in an ice water bath. Mechanical homogenization was performed at 20000 r / min for 10 s, with a rest period of 30 s, and this process was repeated three times to prepare a 10% liver homogenate. Another 10% liver homogenate was used to prepare a backup 5% liver homogenate. Both were centrifuged at 3000 r / min for 10 min, and the supernatant was used for detection of various indicators (reduced GSH, TG, MDA). The detection and calculation methods of MDA and reduced GSH were based on the instructions for the kit of Nanjing Jiancheng Bioengineering Institute. TG was detected using a BS-330E fully automatic biochemical analyzer.

[0142] 2. Result detection

[0143] 2.1 Evaluation Method

[0144] Microscopic examination: record the pathological changes of cells from one end of the liver, and use a 40x objective lens to continuously observe the entire tissue section. Mainly observe the distribution, range and area of ​​fat droplets in the liver.

[0145] 2.2 Scoring Criteria

[0146] The area occupied by various lesions in each visual field was recorded separately, and the total score of lesions in the observed visual field was accumulated.

[0147] Scattered and sparse lipid droplets in hepatocytes 0 points

[0148] No more than 1 / 4 of the hepatocytes contain lipid droplets 1 point

[0149] No more than 1 / 2 of the hepatocytes contain lipid droplets 2 points

[0150] No more than 3 / 4 of the hepatocytes contain lipid droplets 3 points

[0151] Liver tissue is almost replaced by lipid droplets 4 points

[0152] 2.3 Result determination: If any of the conditions are met, it can be determined that the test sample has an auxiliary protective effect on alcoholic liver damage.

[0153] 2.3.1 The results of the three liver detection indicators, MDA, reduced GSH and TG, were positive.

[0154] 2.3.2 Any two of the three indicators of liver MDA, reduced GSH and TG are positive and the results of pathological histological examination are positive.

[0155] 2.4 Experimental data statistics: SPSS26 software was used to test the homogeneity of variance of the original data of each experiment. If the requirements of "homogeneity of variance" were met, the data were statistically processed using one-way analysis of variance and pairwise comparison of the means between multiple experimental groups and a control group. Appropriate variable transformation was performed on data with non-normal distribution or uneven variance. Statistical processing was performed after the requirements of "normal distribution and homogeneity of variance" were met. If the conditions were still not met, non-parametric tests were used.

[0156] 3. Test results

[0157] 3.1 Effect of nano-modified negative hydrogen tablets on the body weight of mice

[0158] As shown in Table 1, there were no significant differences in body weight and weight gain between the mice in each dose group and the model control group and those in the blank control group (P>0.05).

[0159] Table 1 Effect of nano-modified negative hydrogen tablets on mouse body weight (X+SD)

[0160]

[0161] 3.2 Effects of nano-modified negative hydrogen tablets on MDA, reduced GSH and TG in mouse liver homogenate

[0162] As shown in Table 2, after mice were given 50% ethanol at a dose of 12mL / kg.BW, the MDA value of the model control group increased, the reduced GSH value decreased, and the TG value increased. Compared with the blank control group, the differences were significant (P<0.01), indicating that the modeling of this experiment was successful. Compared with the model control group, the MDA value of each dose group decreased, but the difference was not significant (P>0.05); the reduced GSH value of each dose group increased, and the difference was significant (P<0.01); the TG value of each dose group decreased, and the difference was significant (P<0.01). It can be determined that the results of the two indicators of GSH and TG are positive.

[0163] Table 2 Effects of nano-modified negative hydrogen tablets on MDA, reduced GSH and TG in mice (X+SD)

[0164]

[0165] Note: When each dose group is compared with the model control group, it means P<0.01; when the model control group is compared with the blank control group, ## means P<0.01.

[0166] 3.3 Effect of nano-modified negative hydrogen tablets on mouse liver tissue pathology

[0167] As shown in Table 3, there was a statistically significant difference in the liver fat cell degeneration score between the model control group and the blank control group (P<0.01), indicating that the mouse alcoholic liver injury model was successfully established. Compared with the model control group, the degree of hepatic fat degeneration in each dose group was reduced, and the high and medium dose groups were significantly different from the model control group (P<0.05), and the pathological histological indicators could be judged as positive.

[0168] Table 3 Effect of nano-modified negative hydrogen tablets on mouse liver tissue pathological histology (X+SD)

[0169]

[0170] Note: When comparing each dose group with the model control group, # indicates P < 0.05; when comparing the model control group with the blank control group, # indicates P < 0.01.

[0171] 4 Conclusion

[0172] Chemical liver injury model was induced in male Kunming mice of SPF grade with 50% anhydrous ethanol. The samples were divided into high, medium and low dose groups (30, 20 and 10 times of the recommended human intake (3.0g / 60kg.BW, i.e. 0.05g / kg.BW) provided by the inspection unit, and blank control group and model control group were set up. The mice were orally gavaged for 30 consecutive days, and various indicators were measured.

[0173] as follows:

[0174] 4.1 There was no significant difference in the weight gain of mice in each dose group and the model control group compared with the blank control group (P>0.05).

[0175] 4.2 The differences in various indicators between the model control group and the blank control group were significant, indicating that the alcoholic liver injury model was successfully established. On this basis, the MDA value of liver homogenate in each dose group was reduced, but the difference was not significant (P>0.05); the reduced GSH value of liver homogenate in each dose group was increased, and the difference was significant (P<0.01); the TG value in liver homogenate in each dose group was reduced, and the difference was significant (P<0.01). The results of the two indicators of GSH and TG were judged to be positive.

[0176] 4.3 The results of liver pathological histology showed that the degree of fatty degeneration of hepatocytes was alleviated in all dose groups, and there was a significant difference between the high and medium dose groups and the model control group (P<0.05).

[0177] Conclusion: The GSH and TG indicators in the liver homogenate of this sample and the results of pathological histological examination were all positive. According to the "Test Method for Auxiliary Protection Function against Chemical Liver Injury" in the "Catalogue of Health Functions Allowed to Be Claimed by Health Foods (2020 Edition) (Draft for Comments)", it can be determined that:

[0178] Nano-modified negative hydrogen tablets have an auxiliary protective effect on alcoholic liver damage.

[0179] In summary, the present invention proposes a nano-modified negative hydrogen tablet and a preparation method thereof, which significantly improves the antioxidant activity and bioavailability of the negative hydrogen tablet through the following technical schemes: the preparation process of negative hydrogen oyster nanopowder is optimized, and subcritical water purification, alkali coating, high-temperature calcination and other treatments are used to improve its specific surface area and activity. A composite sustained-release membrane composed of gelatin, sodium alginate, glyceride, etc. is designed, which can effectively control the sustained release and absorption of negative hydrogen ions. Sodium alginate improves the mechanical strength and stability of the membrane, and glyceride enhances the permeability of negative hydrogen ions. Advanced processes such as high-speed shear granulation and coating tableting are used to further optimize the preparation process of the negative hydrogen tablet, ensuring the stability and consistency of product quality. The results of animal experiments show that compared with the prior art, the DPPH free radical scavenging rate of the nano-modified negative hydrogen tablet prepared by the present invention is increased by 16.4-36.4 percentage points, reaching a high level of 94%. In the alcoholic liver injury mouse model, each dose group showed significant liver protection, increased the content of reduced glutathione in liver tissue, reduced the level of triglycerides, and alleviated the fatty degeneration of liver cells. Therefore, the nano-modified negative hydrogen tablets of the present invention have significant innovation and practical value, and can effectively overcome the problems of low activity, poor sustained release, and low absorption rate of existing negative hydrogen health products, and have broad application prospects for improving human antioxidant capacity, delaying aging, and preventing and treating related diseases.

[0180] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A nano-modified negative hydrogen sheet, characterized in that: It is prepared from the following raw materials in parts by weight:

2. The nano-modified negative hydrogen sheet according to claim 1, characterized in that: It is prepared from the following raw materials in parts by weight:

3. The nano-modified negative hydrogen sheet according to claim 2, characterized in that: It is prepared from the following raw materials in parts by weight:

4. The nano-modified negative hydrogen sheet according to claim 1, characterized in that: The negative hydrogen oyster nano powder is prepared by the following method: Fresh oyster shells are cleaned and placed in subcritical water for purification to remove surface organic matter and heavy metals, wherein the purification treatment is carried out under the conditions of pressure 1.5-15MPa and temperature 180-350℃ for 2-6h, and the purified oyster shells are dried and crushed into particles below 500μm to obtain oyster shell powder; the oyster shell powder is mixed with 2.5-20wt% calcium hydroxide slurry at a weight volume ratio of 0.1-1, and coated for 2-4h to obtain alkali-coated oyster shell powder; the alkali-coated oyster shell powder is placed at a high temperature of 900-1200℃ and calcined for 3-6h to convert it into calcium oxide powder with a core-shell structure, wherein the core part is oyster shell powder. Calcium oxide microparticles converted from oyster shells, wherein the shell part is calcium oxide nanoparticles converted from calcium hydroxide; the calcined calcium oxide powder is ground to reach a nanometer level with an average particle size of 5-10 μm to obtain nanometer-level oyster shell powder; the nanometer-level oyster shell powder is mixed with lecithin E322 and bamboo charcoal powder in a mass ratio of 1:(2-10):(4-5), and ultrasonically dispersed to form a suspension; the suspension is placed in a closed container with magnesium hydride on the bottom for reaction, so that the powder absorbs and enriches hydrogen; an acid-base regulator is added to the hydrogen-enriched suspension to adjust the pH to a weak alkaline of 7.5-8.5; the pH-adjusted suspension is stirred at a low speed, and vacuum freeze-dried to obtain the product.

5. The nano-modified negative hydrogen sheet according to claim 1, characterized in that: The sustained-release film is prepared by the following method: Prepare gelatin, sodium alginate, glyceride, citric acid and bean curd residue in a mass ratio of (30-50):(5-8):(2-3):(1-5):(2-6), add purified water 5-10 times the mass of gelatin, stir and swell at 40-60°C for 2-4 hours to obtain a uniform modified gelatin solution, place the modified gelatin solution in a vacuum degassing machine, degas at 0.08-0.1MPa for 20-40 minutes, evenly coat the modified gelatin solution on a clean glass plate, control the coating thickness to 200-500μm, the coating speed to 5-10cm / s, and dry at 40-60°C for 2-6 hours until the moisture content of the film layer is ≤10%.

6. The nano-modified negative hydrogen sheet according to claim 1, characterized in that: The starch is corn starch.

7. A method for preparing the nano-modified negative hydrogen sheet according to any one of claims 1 to 6, characterized in that: The steps include: The negative hydrogen oyster nano powder, sustained-release film and starch are uniformly mixed and granulated, and then magnesium stearate is added for coating and tableting is performed.

8. The method for preparing the nano-modified negative hydrogen sheet according to claim 7, characterized in that: The mixing time is 20-30 minutes; The weight of water added during the granulation process is 30-50% of the total weight of other substances; The granulation equipment is a high-speed shearing machine, and the granulation time is 5-15 minutes.

9. The method for preparing the nano-modified negative hydrogen sheet according to claim 7, characterized in that: The coating time is 3-5 minutes, and the coating thickness is 0.2mm-0.5mm.

10. The method for preparing the nano-modified negative hydrogen sheet according to claim 7, characterized in that: The tablet pressing equipment is a rotary tablet press, the tablet pressing pressure is 100-300MPa, the tablet weight is controlled to be 500-1000mg, and the tablet pressing speed is 20-50rpm.